Depression after temporal muscle flap: A systematic review of the literature. Issue 7 (July 2019) - Laloze, J.; Brie, J.; Chaput, B.; Usseglio, J.
Abstract: Background: There are several ways to fill the depression created after temporal muscle flap. Historically, many methods have been described but biomaterials are increasingly used for this indication. We conducted a systematic review of the literature on the use of biomaterials to fill this depression. Methods: The databases MEDLINE (via PubMed), Cochrane Library, EBSCO, Web of Sciences and Embase were searched for clinical trial reports, case series, case reports and cohort studies from 1991 to 2015. We conducted a systematic review of the use and efficacy of different biomaterials. Patient satisfaction was systematically researched. Results: We identified 11 articles (196 patients) which were included in the systematic review. The biomaterials used are polymethyl methacrylate (PMMA), polyethylene (PE), lipofilling, Titanium (Ti) and Mersilene Mesh (MM). Complications occurred only with PMMA and MM. Patient satisfaction was rather good in all the studies. Conclusion: There is no evidence of the superiority of one biomaterial over another as there was a lack of high quality studies. More randomized and controlled studies are required to draw conclusions on the matter.